Foreign Exchange Intervention: Has It Been Effective in Indonesia? - Rakhmat, - (Science and Engineering Research Support Society, 2020)
We assess the motive and effectiveness of foreign exchange intervention in stabilizing exchange rate in Indonesia. High volatility of exchange rate and capital flows since the global crises have forced central banks to complement its interest rate response with foreign exchange intervention in managing domestic objectives of inflation and economic growth. Using Two-Stage Least Squares (2SLS) and Generalized Autoregressive Heteroskedasticity (GARCH) models with monthly data from January 2004 to December 2018, we find that the motive of managing volatility of exchange rate is more visible than of managing the exchange rate changes and its misalignment to its fundamental level. We also find that foreign exchange rate intervention has been effective in Indonesia for managing exchange rate in both volatility and its misalignment to the fundamental levels. The results of this paper provide evidences of the efficacy of foreign exchange intervention in dealing with monetary policy trilemma in small-open economy.